2021
DOI: 10.1113/ep089317
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen supercompensation is due to increased number, not size, of glycogen particles in human skeletal muscle

Abstract: Glycogen supercompensation after glycogen-depleting exercise can be achieved by consuming a carbohydrate-enriched diet, but the associated effects on the size, number and localization of intramuscular glycogen particles are unknown. We investigated how a glycogen-loading protocol affects fibre type-specific glycogen volume density, particle diameter and numerical density in three subcellular pools: between (intermyofibrillar) or within (intramyofibrillar) the myofibrils or beneath the sarcolemma (subsarcolemma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 34 publications
1
23
5
Order By: Relevance
“…Although the respective effect of glycogen size and amount on bound water content was not revealed, a complicated change in glycogen structure may make it difficult to predict the relationship between muscle glycogen and bound water. Notably, a recent study indicated that glycogen supercompensation in humans increases glycogen number rather than size [ 50 ]. Second, body water flow, which was not associated with glycogen, should be considered.…”
Section: Muscle Glycogen and Body Hydration Statusmentioning
confidence: 99%
“…Although the respective effect of glycogen size and amount on bound water content was not revealed, a complicated change in glycogen structure may make it difficult to predict the relationship between muscle glycogen and bound water. Notably, a recent study indicated that glycogen supercompensation in humans increases glycogen number rather than size [ 50 ]. Second, body water flow, which was not associated with glycogen, should be considered.…”
Section: Muscle Glycogen and Body Hydration Statusmentioning
confidence: 99%
“…These inherent factors might influence how dietary CHO and energy consumption affect the glycogen storage pattern. In the previous mentioned study by Jensen et al (2021) particle sizes in skeletal muscle fibres are remarkable similar across isocaloric diets differing in CHO content, but a low CHO diet reduces the numerical density in all pools. Therefore, the second aim of the present study was to investigate the effect of lowered carbohydrate and energy intake and subsequent maximal exercise at two different intensities, on glycogen volumetric densities, particle size, numerical density, and localisation within skeletal muscle fibres.…”
Section: Introductionmentioning
confidence: 58%
“…This suggests that female athletes may need to increase energy intake above their apparent (self-reported) or true habitual intake, both to achieve CHO targets and to allow an energy availability that will support an increase in muscle glycogen. Despite the continued investigation of CHO loading protocols, with topics such as the localization or structure of glycogen particles ( 30 ), these have been undertaken with male-only or mixed-sex cohorts. Indeed, no studies of CHO loading involving separate analysis of female participants have been published over the past 15 yr, despite the likelihood of sex-based differences in muscle fibers ( 10 ).…”
Section: Discussionmentioning
confidence: 99%